# If a - b = 4 and a + b = 6, then find ab.

$

{\text{A}}{\text{. 5}} \\

{\text{B}}{\text{. 2}} \\

{\text{C}}{\text{. 45}} \\

{\text{D}}{\text{. 3}} \\

$

Last updated date: 21st Mar 2023

•

Total views: 309k

•

Views today: 6.88k

Answer

Verified

309k+ views

Hint- Here, we will be using elimination method to solve the given two equations in two variables.

Given equations are $a - b = 4{\text{ }} \to {\text{(1)}}$ and $a + b = 6{\text{ }} \to {\text{(2)}}$

The above two given equations have two variables $a$ and $b$.

Adding both the equations (1) and (2), we get

$a - b + a + b = 4 + 6 \Rightarrow 2a = 10 \Rightarrow a = 5$

Put the value of $a$ in equation (1), we get

$5 - b = 4 \Rightarrow b = 5 - 4 \Rightarrow b = 1$

So, the values of the two variables that satisfy the two given equations are $a = 5$ and $b = 1$.

Hence, $ab = 5 \times 1 = 5$

Therefore, the value of $ab$ is 5.

i.e., option A is correct.

Note- These types of problems of two equations in two variables can be solved easily using substitution method or elimination method. In the substitution method, we represent one variable in terms of another variable using one equation and substitute this value in the other equation in order to get the values of both variables.

Given equations are $a - b = 4{\text{ }} \to {\text{(1)}}$ and $a + b = 6{\text{ }} \to {\text{(2)}}$

The above two given equations have two variables $a$ and $b$.

Adding both the equations (1) and (2), we get

$a - b + a + b = 4 + 6 \Rightarrow 2a = 10 \Rightarrow a = 5$

Put the value of $a$ in equation (1), we get

$5 - b = 4 \Rightarrow b = 5 - 4 \Rightarrow b = 1$

So, the values of the two variables that satisfy the two given equations are $a = 5$ and $b = 1$.

Hence, $ab = 5 \times 1 = 5$

Therefore, the value of $ab$ is 5.

i.e., option A is correct.

Note- These types of problems of two equations in two variables can be solved easily using substitution method or elimination method. In the substitution method, we represent one variable in terms of another variable using one equation and substitute this value in the other equation in order to get the values of both variables.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write the 6 fundamental rights of India and explain in detail

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Name the 8 union territories of India

What are merits and demerits of democracy

Define human made resources

What is pollution? How many types of pollution? Define it

A 30 solution of H2O2 is marketed as 100 volume hydrogen class 11 chemistry JEE_Main

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.